Social Buttons and Peer-to-Peer Second-Hand Marketplace Interactivity on Letgo - Özcan, Erhan; Şimşek, Burcu (Communication Today, 2022)
Despite appearing in different forms with multiple endemic functions in digital peer contexts, prior research is engrossed with a focus on the Like and Share buttons. Therefore, it pays scant attention to the remaining social button variants, which are brought into play by users on a day-to-day basis in the social web. Addressing this lacuna, this study seeks to contribute to our understanding of the online buttonised usage phenomenon, by examining social buttons usage in the context of the Letgoconsumer-to-consumer online marketplace. Drawing on qualitative interviews with 17 ‘Letgoers’ and online participant observation, the study shows that social buttons represent an enabling and facilitation mechanism, which temporarily eliminates the digital user need (i.e., orthographic need) to type and retype. This conduction culminates in specific user behaviour, which is motivationally shaped by the digital need – least effort – fulfillmentequation. The study further claims that while peer-to-peer marketplace activity onLetgonecessarily involves user participation, it is alienated in the sense that the buttonised process is beyond the reach of Letgoers’ knowing and meaningful (digital) intervention. Hence, it should rather be understood as a practice of delegation to algorithmic conduction.